Studies on Coordination Behaviour of Co(II), Ni(II) and Cu(II) Complexes of Semicarbazones and Thiosemicarbazones - Jha, S.; Verma, R.P. (Asian Journal of Chemistry, 2010)
Co(ll), Ni(II) and Cu(II) complexes of 2-hydtoxy-5-methyl acetaphenone/2- hydtoxy-3,4-dimethoxy acetophenone semicarbazone, thiasemicarbazone and amino guanidine have been prepared and characterized. Antimicrobial activities of the synthesized complexes have also been studied.